Rural Students’ Barriers in Learning English during the COVID-19 Pandemic - Ali Akbarjono; Zelvia Liska Afriani; Ria Annisa (Journal of English Language Teaching, Linguistics, and Literature Studies, 2022)
Rural Students Barriers in Learning English during the COVID-19 Pandemic Research paper: this research describes the obstacles that students who reside in rural areas experience and how they overcome those obstacles. Ten students from the English Education Investigation Program were the subjects of this study. The author employed a qualitative technique and a case study design. The writer utilized an online questionnaire, interviews, and documents to collect data. The data findings revealed that practically all students faced social, institutional, dispositional, and epistemological difficulties. The data also indicated that students face nine obstacles, such as an unsupportive learning environment, a network difficulty, time management, a significant assignment, a cost, students' challenges in learning English, a learning style issue, and students lack of desire. They overcome such hurdles in various ways, depending on the individual. This study's findings will impact the teaching and learning processes. The professor is required to assist pupils in overcoming obstacles. The study also recommended that students pay more attention to the online learning experience. The study also contributes to the realm of language, and future researchers should pay close attention to this phenomenon.Keywords: Rural Students, Barriers, Online Learning, Covid-19 Pandemic